A Lexical Semantic Analysis of Political Risk Lexis in BBC News: "Trump's Confidence Is Undimmed-But Every Iran Option Comes with Risk - Tessaria Simorangkir; Bernieke Anggita Ristia Damanik (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to analyze political risk lexis in the BBC News article entitled “Trump's Confidence Is Undimmed – But Every Iran Option Comes with Risk.” The focus of this research is to identify the lexical items related to political risk and examine their meanings using a lexical semantic approach. This study employs a descriptive qualitative research design, as it seeks to interpret the meanings of words within their context rather than to quantify data. The data are taken from a BBC News article and collected using a documentation technique by identifying words and phrases that represent political risk. The analysis reveals that several key lexical items, such as risk, threat, danger, uncertainty, and escalation, are used to construct the concept of political risk in the text. These lexical items are analyzed based on their denotative, connotative, and contextual meanings. The findings show that risk is the most dominant lexical item, supported by other related words that emphasize different dimensions of political instability. Furthermore, the study finds that these lexical items function not only to describe events but also to emphasize uncertainty, construct a perception of danger, and influence readers’ interpretations of the political situation. In addition, the study demonstrates that lexical choices play a crucial role in media discourse, particularly in framing political issues. The use of political risk lexis in the article contributes to constructing a narrative of instability and complexity in the United States–Iran conflict. Therefore, this study highlights the importance of lexical semantic analysis in understanding how language is used to shape meaning and influence public perception in media texts.